Construction and facility management of large MEP projects using a multi-Scale building information model. (October 2016) - Hu, Zhen-Zhong; Zhang, Jian-Ping; Yu, Fang-Qiang; Tian, Pei-Long; Xiang, Xue-Song
Highlights: We addressed the insufficiencies of the current applications in the CM and FM of large MEP projects. We proposed a multi-scale BIM consisting of several macro-, micro- and schematic-scale information models. We developed two systems to improve CM and FM utilizing the multi-scale BIM. The model and systems are successfully applied to a real-world airport terminal. Abstract: Several challenges have been found in the current applications of building information modelling/model (BIM) technology in large-scale mechanical, electrical and plumbing (MEP) projects, such as the huge modelling workloads of MEP models and details, untapped potential in supporting cooperative construction management with multiple participants and insufficient functions for intelligent facility management. This paper proposes a multi-scale solution to address the insufficiencies of the current applications in the construction and facility management of MEP projects. Particularly, a practical multi-scale BIM consisting of several macro-, micro- and schematic-scale information models is described in detail with the required information of the MEP components according to the schema of industrial foundation classes. Based on this model, the paper presents a BIM-based construction management system to provide virtual construction scenes with appropriate scales for various participants to communicate and cooperate, as well as a BIM-based facility management system to share information delivered from previous phases and improve the efficiency and safety of MEP management during the operation and maintenance period. The application in a real-world airport terminal illustrates that the proposed model and two systems can support collaborative construction management and facility management with multi-scale functionalities among participants. This paper proposes a series of feasible models and techniques to promote BIM application in large MEP projects.